PERAN PEMUDA DALAM PENGEMBANGAN DESA WISATA CARANGSARI DI KABUPATEN BADUNG: PERAN PEMUDA DALAM PENGEMBANGAN DESA WISATA CARANGSARI DI KABUPATEN BADUNG - I Putu Yogi Pradnyana; Luh Yusni Wiarti; Ida Bagus Putra Negarayana (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Youth generation is an important aspect in development, including in the village scope, because youth are also part of the community elements. Youth with all its advantages is expected to be a link between local wisdom and the needs of tourists. In developing tourism in Carangsari Tourism Village, of course, it is necessary to involve the role of youth as part of the community who have creativity, innovation, and energy in the tips of the Carangsari Tourism Village development program. This study aims to determine the role of youth in the development of Carangsari tourism village. This research uses descriptive analysis method. This study used 13 resource persons including youth, village government, and tourism village managers. The result of this research is that youth is an important player in the role of Carangsari Tourism Village development. They are actively involved in playing a role in various aspects of development, from planning and innovative ideas, implementing activities, to monitoring and evaluation. Youth also benefit from the development of the tourism village, such as employment opportunities, public facilities, and improved quality of life. These findings suggest that youth have great potential to contribute to the development of tourism villages.